DZIELIMY SIĘ DOŚWIADCZENIEMAnterior mediastinal abscess as a complication of severe car accident - Wojtuń, Kazimierz; Kądziołka, Wojciech; Kobak, Grzegorz; Kądziołka, Joanna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
We describe a case of 61-year old patient admitted to the General Thoracic Departments of Rzeszów because of the substernal mediastinal abscess, chest-wall phlegmon and sepsis after trauma of the anterior chest wall in the car accident.